(untitled) (Revista Científica Compendium, 2021)
The present exploratory-descriptive study aimed to characterize the management control system, from the perspective of the Beyond Budgeting model. This study was carried out in the fruit concentrate manufacturers of the Yaracuy State, Venezuela. The purpose was to respond to the regulatory economic environment. The theoretical approaches, principles, characteristics, functions and benefits on the model in question were considered. Direct observation and interview as data collection techniques were used. The results establish that organizations do not have a defined management control system. The traditional management control system is more rigid. For this reason, the application of the Beyond Budgeting model with the support of the balanced scorecard is recommended as it is more dynamic. Additionally, this system guarantees manufacturers to obtain timely and accurate information for decision-making and facilitates the adaptation to constant changes in the environment to guarantee their sustainability.